Sex, drugs and rock 'n' roll in the Dutch Golden Age - Roberts, Benjamin, 1965- (Amsterdam Univ Press, 2017)
Sex, Drugs and Rock 'n' Roll in the Dutch Golden Age' focuses on the generation of rich young men that grew up in the seventeenth century in the Dutch Republic. These men had more money to spend on clothes, music, and recreation than the generation before them. This fascinating account of male adolescence in the Dutch Golden Age reveals how young men including Rembrandt van Rijn disregarded conservative values and rebelled against the older generation, and consequently created a new youth culture that was similar to the one of the 1960s. They had long hair, wore colorful and extravagant clothing, and started taking drugs. Theirs was the first generation in European history to smoke tobacco. Moreover, they defied conventional norms and values with their promiscuity and by singing lewd songs in their free time.